Disease incidence of shot-hole disease of plum in two training systems - Molnár, Csengőné Bianka (Acta Agraria Debreceniensis, 2023)
Of the foliar diseases of European plum, Wilsonomyces carpopilus is the most commonly occurring fungal pathogen. The aim of this two-year study was to investigate the susceptibility of ‘Čačanska lepotica’ plum variety to shot-hole disease (Wilsonomyces carpophilus) in two different training system with 4 x 1.5 m and 6 x 3 m tree spacings. The obtained results showed that the cultivar is susceptible to this disease and by the end of the vegetational period disease incident was above 50% in both years in both tree spacings. In 2018 disease incidence was higher in both spacing than in 2019, reaching almost 90% at the 4 x 1.5 m tree spacing plot. There were few significant differences between high and low density tree spacings. The results highlighted the importance of inoculum accumulation late in the season.